Achieving Preallocation: Turn Transition Practices in Board Games. Issue 2 (7th February 2021) - Hofstetter, Emily
ABSTRACT: This paper contributes an analysis of practices for managing a preallocated turn-taking system in board games, expanding existing studies of preallocation beyond question-answer sequences. Although board games have existed for thousands of years across human cultures, and despite being a widely used method of data elicitation in many fields of research, there are few studies of how adults accomplish play. Using conversation analysis, this paper demonstrates how participants organize transition between board-game turns, finding that participants treat the game turns as analogous to the organization of pre- and post-possible completion. However, the preallocated nature of game turns results in alternate sense making concerning delays and overlap, especially where such occurrences threaten the achievement of the activity. Data are in English.